HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG ALAT KONTRASEPSI BAWAH KULIT (AKBK) DENGAN SIKAP DALAM PEMILIHAN AKBK DI UPTD PUSKESMAS DAWAN I KLUNGKUNG - Ni Ketut Raiani; Ni Nyoman Budiani; Gusti Ayu Eka Utarini (Jurnal Ilmiah Kebidanan Imelda, 2024)
The increasing population in Indonesia makes it difficult for the government to reduce the maternal mortality rate (MMR). One effort that can be made is a family planning (KB) program. The aim of this study was to determine the relationship between third trimester pregnant women's knowledge about implants and attitudes towards implant selection at the Dawan I Klungkung Community Health Center UPTD. This research uses correlational analytics with a cross-sectional approach. The research was carried out in the 2nd week of March to the 4th week of April 2024. Samples were taken using purposive sampling with a total of 61 respondents. Research instrument with questionnaire. The results of univariate data analysis showed that mothers were aged 20-35 years (88.5%), higher education category (65.6%), private work (50.8%), multipara (62.3%), good knowledge (67 .2%) and positive attitude (54.1%) while bivariate uses a contingency test with a p value <0.05. The conclusion of this study is that there is a relationship between third trimester pregnant women's knowledge about implants and attitudes towards implant selection. It is hoped that the Community Health Center can increase outreach activities related to the importance of contraceptive implants.